(untitled) (Heritage, 2025)
Тhe provisions on the appointment of an ex officio defence counsel in cases of compulsory defence are not essential for criminal proceedings. However, if the provisions on the engagement of a defense attorney in situations where his presence is necessary (mandatory defense) are not respected, serious problems will inevitably arise that will result in the fact that no decision of the public prosecutor’s office and the court regarding the defendant would be valid or lawful. In this paper, we have briefly analyzed the provisions of the Criminal Procedure Code that relate to the topic of this paper and pointed out possible problems and doubts that may arise. These are primarily situations concerning the relationship between the defendant and the appointed ex officio defense attorney, their cooperation, the search for another ex officio defense attorney by the defendant, possible disagreements between them and potential obstruction and abuse of this institute, primarily by the defendant (the so-called buying of time), for the sake of a more favorable outcome of the criminal proceedings itself. In this regard, several such situations were pointed out and how to overcome these doubts and possible problems that are otherwise not covered (foreseen) by the provisions of the CPC. There is also a brief overview of the so-called Criminal Procedure Code. Kosovo in the part that regulates these provisions, and the specifics and differences in relation to the Criminal Procedure Code of the Republic of Serbia. It should be pointed out that despite these possible doubts and problems, the provisions in the Criminal Procedure Code on the appointment of ex officio defense counsel are well thought out, as well as the reasons why defense is mandatory. Therefore, there were no significant differences in relation to the previously applicable laws on criminal procedure. This statement indicates that these provisions have proven themselves well over the decades of their validity and that there was no need for any major changes and additions to this current Criminal Procedure Code. However, the CPC cannot cover all life situations in which public prosecutor’s offices and courts can find themselves when deciding on the appointment (and even dismissal) of a defense attorney ex officio. Fortunately, these obstacles are not common, but they can create a problem in criminal proceedings. Given that no legal solutions are provided for some situations, public prosecutor’s offices and courts resolve them in each specific case, taking care not to allow the abuse of procedural rights by the defendant, which may lead to the statute of limitations of criminal prosecution, but at the same time taking care not to violate the rights of the (mandatory) defense of the defendant. It would be ungrateful to offer some new solutions in terms of appointing a defense attorney ex officio in the case of mandatory defense, because objectively all situations that are real and frequent, life are covered. Expanding with some new situations would not contribute to improvement, and case law has shown that there is no need for it.